ПОБУДОВА СИСТЕМИ АКТИВНОЇ КОМПЕНСАЦІЇ ГІРОСКОПІЧНОЇ РЕАКЦІЇ У ВИСОКООБЕРТОВОМУ ЕЛЕКТРОПРИВОДІ - Антонов, О.Є.; Акинін, К.П.; Кіреєв, В.Г. (Інститут електродинаміки Національної академії наук України, 2017)
The principal approaches to the construction of a control system for the rotor speed, which compensates the action of the gyroscopic moment in an electric drive with a large kinetic moment, are determined. A feature of the control system is the tracking of the rotation of the compensating rotor on the frequency of the main drive motor. In this case, the rotational speeds of the main and compensating rotors, as a rule, do not coincide. The choice of the speed of the compensating rotor is based on the condition of minimizing its volume and mass. References 7, figures 4.